MOTIF PENGUSAHA MUSLIM BISNIS KULINER PERSPEKTIF ALFRED SCHUTZ; STUDI KASUS LUBNA CAKE & CAFE - Sismanto, Sismanto; Siswanto, Siswanto; Djalaluddin, Ahmad; Andriani, Sri; Rikza, Abdullah (At-Tawazun, Jurnal Ekonomi Syariah, 2024)
This study aims to analyze the motives of Muslim entrepreneurs in implementing mujāhadah (spiritual struggle) in their culinary business practices, using Alfred Schutz's phenomenological perspective. The study employs a qualitative approach with a case study design, focusing on Lubna Cake & Cafe in East Kutai. Data were collected through in-depth interviews, direct observation, and document analysis to explore the "because of" and "in order to" motives that influence business decisions. The findings reveal that past experiences, family background, and spiritual beliefs shape the “because of motives” that affect business practices, such as work ethic and dedication in managing the business. Meanwhile, the "in order to motives" reflect long-term aspirations, such as business expansion, improving employee welfare, and making positive social contributions to the surrounding community. This study provides theoretical contributions to understanding the integration of Islamic values in business and offers practical references for Muslim entrepreneurs seeking to combine spiritual values with sustainable business success. The findings also serve as a guide for researchers and practitioners to further explore the application of Islamic values in broader business contexts.